On the Value of Soil Resources in the Context of Natural Capital and Ecosystem Service Delivery. Issue 3 (10th June 2014) - Robinson, D. A.; Fraser, I.; Dominati, E. J.; Davíðsdóttir, B.; Jónsson, J. O. G.; Jones, L.; Jones, S. B.; Tuller, M.; Lebron, I.; Bristow, K. L.; Souza, D. M.; Banwart, S.; et al.
Abstract : The ecosystem services approach endeavors to incorporate the economic value of ecosystems into decision making. This is because many natural resources are subject to market failure. As a result, many economic decisions omit the impact that natural resource use has on the earth's resources and the life support system it provides. Hence, one of the objectives of the ecosystem services approach is to employ economic valuation of natural resources in micro‐ and macroeconomic policy design, implementation, and evaluation. In this article we examine valuation concepts, and ask why we might attempt to economically value the contribution of soils to the provision of ecosystem services. We go on to examine economic valuation methods and review economic valuation of soils. By surveying prices of soils on the web we are able to make a first, limited global assessment of direct market value of topsoil prices. We then consider other research efforts to value soil. Finally, we consider how the valuation of soil can meaningfully be used in the introduction of improved resource management mechanisms such as decision support tools on which valuation can be based, within the UN's System of Environmental and Economic Accounts (SEEA) and policy mechanisms like Payments for Ecosystem Services (PES).